Task-Based Learning Approach in Teaching Writing at Indonesia Junior High School - Risty Suci Ramadayanti; Muhammad Basri Jafar; Abdul Halim (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2024)
This research was aimed (1) To know the teacher’s perception towards task-based learning approach in teaching writing, (2) To know the implementation task-based learning approach in teaching writing, and (3) To know task-based learning approach impact on students’ writing skills. This research used a descriptive qualitative method. The subject of this research was an English teacher and 20 students in the eighth grade at SMPN 1 Mimika Timur, Papua Tengah. The data was collected through observation checklist and semi-structure interviews. The result of this research showed that (1) the teacher has positive perception about task-based learning approach, namely can make students more active, more enthusiasm, and enjoyable, (2) implementation task-based learning approach in teaching writing at Indonesia junior high school the teacher used three stages, namely pre task, task cycle, and language focus, and (3) task-based learning gave positive impact on students writing skill, namely students can express their ideas, write their task more interesting, they are not afraid to share their ideas, can organize tasks, can avoid ambiguity, get new vocabulary, improve in language use, ensure the right form of words when writing and also enhance their knowledge in mechanical skills, such as capitalization, punctuation, and spelling.